2018
DOI: 10.20964/2018.03.152
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical determination of lead(II) ions in hot spring water based on a multi-walled carbon nanotube-modified glassy carbon electrode

Abstract: The present study reports the fabrication of a carbon nanotube/Nafion composite film (MWNT/Nafion)-modified glassy carbon electrode (GCE) along with its excellent performance in the analysis of Pb 2+ (favorable catalytic activity, large surface area, high cation exchange capacity, and strong adsorption ability). The stripping peak current of Pb 2+ was greatly increased at the MWNT/Nafion-coated GCE compared with the bare and Nafion-coated GCEs. The optimization of different parameters was also carried out, inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 46 publications
0
1
0
1
Order By: Relevance
“…Với những tác hại nghiêm trọng của chì đến sức khỏe con người như vậy nên việc xác định hàm lượng chì trong các mẫu, nhất là mẫu nước là rất cần thiết. Có nhiều phương pháp xác định chì như phương pháp phổ hấp thu nguyên tử [5][6][7], phương pháp quang phổ phát xạ nguyên tử plasma [8], phương pháp đo phổ huỳnh quang nguyên tử [9], phương pháp điện hóa [10], … Thông thường các phương pháp này cần phải thực hiện bước tách chiết và làm giàu chì trước khi phân tích. Trong những năm gần đây, việc kết hợp phương pháp phổ hấp thu nguyên tử với các kỹ thuật làm giàu ion chì trong mẫu rất được chú trọng phát triển [11][12][13].…”
Section: Mở đầUunclassified
“…Với những tác hại nghiêm trọng của chì đến sức khỏe con người như vậy nên việc xác định hàm lượng chì trong các mẫu, nhất là mẫu nước là rất cần thiết. Có nhiều phương pháp xác định chì như phương pháp phổ hấp thu nguyên tử [5][6][7], phương pháp quang phổ phát xạ nguyên tử plasma [8], phương pháp đo phổ huỳnh quang nguyên tử [9], phương pháp điện hóa [10], … Thông thường các phương pháp này cần phải thực hiện bước tách chiết và làm giàu chì trước khi phân tích. Trong những năm gần đây, việc kết hợp phương pháp phổ hấp thu nguyên tử với các kỹ thuật làm giàu ion chì trong mẫu rất được chú trọng phát triển [11][12][13].…”
Section: Mở đầUunclassified
“…Wang et al [68] reported that the diminished peak current at high pH values was ascribed to the hydrolysis of Pb 2+ in alkali solution. It was suggested that when greater amounts of alkali solution are used, the possibility of forming lead hydroxide increases as white precipitation increases, [69] meaning that a broad or multiple stripping peak may appear due to the formation of different lead hydroxides. [70] For this reason, a pH of 5.5 was used for all subsequent measurements.…”
Section: Study Of the Influence Of The Variation In Ph Of The Solutionmentioning
confidence: 99%